Testing a numerical glacial hydrological model using spring speed-up events and outburst floods - Kessler, Mark A.; Anderson, Robert S. (Geophysical research letters, 2004)
We describe a numerical model of a glacial‐hydrologic system that reproduces the salient features of two hydrological and ice motion events commonly observed on temperate alpine glaciers. These include the pattern of ice sliding and water discharge characteristic of spring speed‐up events, and the triggering and structure of outburst floods from ice‐marginal lakes. These behaviors result from strong internal feedbacks between water storage in englacial macro‐pores or an ice‐marginal lake, ice motion by sliding and deformation, and a subglacial hydrologic system consisting of a slow‐flow linked cavity network and a fast‐flow centerline conduit.